İslam Tarihinde Arap Milliyetçiliği Üzerine Oryantalist Bir Bakış: Patricia Crone ve Metodu/An Orientalist Perspective on Arab Nationalism in Islamic History: Patricia Crone and her Method - Öznur Özdemir (Oksident, 2025)
In Western academia, scholars who study Islamic history are generally called Islamic historians. However, non-Muslim researchers focusing on this field are often referred to as Orientalist Islamic historians, or simply as Orientalists. One of the main topics explored by these scholars has been the political context of Islam’s emergence and expansion. Yet, due to the influence of Eurocentric historiography, their findings have frequently been shaped by Orientalist perspectives. Patricia Crone (1945–2015), known for her revisionist approach, stands out as a prominent Orientalist Islamic historian. Her research, particularly on the mawālī and Arab nationalism in Islamic societies, has significantly influenced the field. Crone’s works and her critical methodology have sparked considerable academic debate, with her strong skepticism towards Islamic sources receiving particular criticism. While some studies have examined various aspects of Crone’s Orientalist views, there has not yet been a comprehensive study that specifically analyses her impact on Western Islamic studies, especially in relation to her views on Arab nationalism. This article aims to examine Patricia Crone’s academic career and works, evaluate her impact on Western Islamic studies, and analyze her methodology through an examination of one of her studies on Arab nationalism. This study, titled “Mawālī and the Prophet’s Family: An Early Shī‘ite View”, is a translation and analysis of a letter attributed to Mu‘awiya and addressed to Ziyād b. Abīhi. In the letter, Mu‘awiya instructs Ziyād to treat the mawālī harshly. While making this suggestion, Mu‘awiya refers to earlier policies toward non-Arabs. Crone interprets these references to demonstrate how and when Arab nationalist sentiments were articulated in Islamic society. This particular study has been chosen due to its close connection with the topic of the mawālī, which Crone specialized in during her doctoral studies, and because it represents one of her final publications prior to her death. In this part of the article, Crone’s evaluation of Arab nationalism in Islamic society will be discussed, with a specific focus on her interpretation of the expressions found in the letter. Finally, the article will examine Crone’s methodological approach to Islamic historical sources by analysing both her views in similar studies, and the criticisms directed at her by other historians. In doing so, it aims to introduce a prominent scholar known in the West for her distinctive views on Islamic history to researchers in this field, and to provide a critical evaluation of her perspectives and methodology.